Situate, manipulate, fabricate : an anthology of the influences on architectural design and production - Schwartz, Chad (New York, NY : Routledge, 2020)
"This anthology of selected works outlines three critical instigators of architecture, all tied directly to the tectonic makeup of our built environment - place, material, and assembly. These catalysts provide the organizational framework for a collection of essays discussing their significant influence on the processes of architectural design and construction. With content from a diverse collection of notable architects, historians, and scholars, this book serves as a theoretical structure for understanding the tectonic potential of architecture. Each chapter is thematically driven, consisting of a pair of essays preceded by an introduction highlighting the fundamental issues at hand and comparing and contrasting the points of view presented. Situate, Manipulate, Fabricate offers an opportunity to explore the essential topics that affect the design and construction, as well as the experiential qualities, of our built environment"--
Groundwork / Robin Dripps -- Material is not a finish / Kengo Kuma -- Excerpts from The nature and art of workmanship / David Pye.
OCLC-licensed vendor bibliographic record.
Keywords: Architecture -- Philosophy; Place (Philosophy); Building materials; Workmanship; ARCHITECTURE / General; ARCHITECTURE / Criticism; ARCHITECTURE / Reference